PRESENTATION OF WINE CONSUMPTION CULTURE IN WESTERN EUROPEAN CINEMA - Barnyak, Anastasiia; Korobko, Margarita (УКРАЇНСЬКА КУЛЬТУРА : МИНУЛЕ, СУЧАСНЕ, ШЛЯХИ РОЗВИТКУ, 2024)
Background. The theme of alcohol consumption is deeply embedded in human life. Wine embodies cultural symbols, family traditions, and aspects of personal identity. Cinematic portrayals of alcohol undeniably shape individual perceptions, as film reflects societal sentiments while also shaping new realities that resonate with audiences. The way wine is romanticized or rejected in cinema can significantly impact people's attitudes toward it. This study does not advocate for abstinence or indulgence but rather uses alcohol as a lens to examine cultural phenomena, particularly within the realm of cinema. Objective. Depiction of wine consumption culture in Western European cinema. Methods. A systematic approach was employed to address the issue comprehensively. A systemic-functional method was applied to classify cinematic symbols of wine depiction based on the structure of Ortega y Gasset, highlighting common and distinctive features. Additionally, semiotic, comparative, axiological methods, and content analysis were used. Results. Cinema, as a multifaceted medium, mirrors societal realities and shapes alternative ones. Its symbolic power transforms ordinary practices, such as wine consumption, into potent cultural and narrative tools. Wine, a universal symbol of luxury, pleasure, and social status, serves as both a plot device and a character in global cinema, reflecting attitudes toward alcohol across eras. Drawing from J. Ortega y Gasset's analysis of wine-themed art, wine's cinematic symbolism oscillates between human unity with nature, divine celebration, and moral degradation. European cinema often portrays wine with reverence, especially in French and Italian films, which link it to familial ties, heritage, and passion for craftsmanship. Wine's dual nature – symbolizing joy and disillusionment – makes it a compelling cinematic element. From fostering unity in idyllic settings to catalyzing conflicts and exposing existential truths, wine remains a reflection of human culture. Cinema, through its depictions of wine, not only captures but influences societal perceptions, offering a profound commentary on humanity's relationship with tradition, luxury, and morality. Conclusions. Wine in Western European cinema symbolizes familial continuity, luxury, and celebration, serving as both a narrative tool and cultural commentary. Films romanticize wine’s natural purity, explore its connection to human relationships, and highlight societal attitudes. Occasionally, wine represents moral decline, reflecting broader challenges and dilemmas within culture and human nature.